2008
DOI: 10.1007/s00784-007-0173-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of non-cavitated approximal caries lesions in digital images from seven solid-state receptors with particular focus on task-specific enhancement filters. An ex vivo study in human teeth

Abstract: The aim of this study was to compare detection of non-cavitated approximal caries lesions in images from seven solid-state intraoral digital receptors, with particular focus on two task-specific enhancement filters. One hundred and sixty approximal non-cavitated surfaces were radiographed under standardized conditions using the following seven intraoral solid-state digital receptors: two CMOS systems, Schick CDR-APS, and Kodak RVGui; and five CCD systems: Visualix, VistaRay, Dixi2, Sidexis, and Dr. Suni Plus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 21 publications
3
36
1
1
Order By: Relevance
“…As seen in the results presented in the present manuscript, the application of different radiographic filters did not result in an improvement in the diagnosis of caries, corroborating the results found by Takeshita et al 3 Haiter-Neto et al 13 Booshehry et al 17 Belém et al 19 and…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As seen in the results presented in the present manuscript, the application of different radiographic filters did not result in an improvement in the diagnosis of caries, corroborating the results found by Takeshita et al 3 Haiter-Neto et al 13 Booshehry et al 17 Belém et al 19 and…”
Section: Discussionsupporting
confidence: 91%
“…These programs allow image manipulation, such as adjustment in brightness and contrast, determination of the gray level, inversion of gray tones, application of pseudocolors, among other features. 3,[11][12][13] Therefore, as far as we know, few studies have compared the different digital image filters in the diagnosis of secondary caries lesions, with the influence of horizontal angulation. The aim of the present research was to evaluate the accuracy of diagnosing secondary caries artificially created in the pulp wall of premolars with mesio-occlusal-distal (MOD) restorations made with resin composite, by means of digital image filters, with alteration in the horizontal angulation in the interproximal radiographic technique, using a digital radiographic sensor complementary metaloxide-semiconductor (CMOS).…”
Section: 5005/jp-journals-10024-1761mentioning
confidence: 99%
“…These studies showed any effects on diagnostic accuracy by using the tested filters. 10,11,19 Another study concluded that some filters have improved the detection of caries lesions, whereas others cannot be recommended. 20 However, to the best of the authors' knowledge, this is the first attempt to evaluate the effect of different image filters on the detection of non-displacing longitudinal root fractures in CBCT images.…”
Section: Discussionmentioning
confidence: 99%
“…5 Different studies have analysed the effects of enhancement radiographic digital images to detect longitudinal root fractures and oclusal and proximal caries lesions. [9][10][11][12][13] Other studies have evaluated the effect of different digital image filters on various relevant anatomical structures. 14,15 Some other studies have evaluated effects of sharpen filters on CBCT images to detect transverse root fractures and external root resorption.…”
Section: Introductionmentioning
confidence: 99%
“…No statistically significant difference was found between original and enhanced images in terms of diagnostic accuracy. 18,19 Accuracy of the detection of proximal enamel caries lesions using three intraoral storage phosphor plate digital systems (DenOptix, Gendex Dental Systems) and Digora FMX with white and blue plates (Soredex, Helsinki, Finland) has been compared to that of Insight film. 20 There was no significant difference in the diagnostic accuracy among Insight film and the Digora and DenOptix digital systems for proximal enamel caries.…”
mentioning
confidence: 99%